Unmet need for contraception among married women of reproductive age in rural Maharashtra - Tapare, V. S.; Parande, Malangori A.; Borle, Pradip S. (International Journal Of Community Medicine And Public Health, 2017)
Background: The concept of “unmet need” for contraceptive points to the gap between women’s reproductive intention and their contraceptive behavior. About 12.8% of currently married women in India have an unmet need for contraception. The present descriptive cross-sectional survey was initiated to address the research questions regarding unmet need for contraception among married women of reproductive age group in rural Maharashtra. Methods: 400 married women of reproductive age living in rural area of Sangli district of Maharashtra state interviewed. The survey based on women’s response to survey questions regarding family information, fertility profile and attitude and practice of contraceptive use. Expanded formulation used for surveys to assess the size and characteristics of unmet need group, dividing it into distinct subgroups and to explore the reasons for unmet need using in-depth qualitative research. Data analyzed with absolute number and percentage of women having unmet need which is useful to set priorities in program for effective fertility control. The data was tabulated and analyzed using MS Excel. Results: Total unmet need for contraception was found 27.50% women, which comprises need for ‘spacing’ in 12.25% women, need for ‘limiting birth’ in 13.25% women and need for ‘appropriate contraception’ in 2.0% women among 400 married women of reproductive age. Most unmet need among younger women is for spacing birth (67.18%) while in older women above age 30 year; most unmet need (68.18%) is for limiting birth. The education of women does not affect significantly the unmet need for spacing and limiting birth. After first child the unmet need for spacing decreases with each additional child. On the contrary unmet need for limiting birth increases with each additional child after first child and it was maximum (96.55%) among women having 3 or more children. Conclusions: The study group expresses multiple reasons for the unmet need. Many of the reasons are not directly related to contraception. Most women with unmet need desire to use contraception in future favours spacing methods. People should have access to good quality information and services. Health education and motivation is needed to overcome these causes.